Organochlorine Levels in Plasma and Risk of Multiple Myeloma. Issue 10 (October 2018) - Weber, Leah; Song, Kevin; Boyle, Terry; Gaudreau, Éric; Lai, Agnes; Sutherland, Heather J.; LeBlanc, Alain; Spinelli, John J.
Abstract : Objective: The aim of this study was to estimate the association between organochlorine pesticides and polychlorinated biphenyls (PCBs) and multiple myeloma (MM). Methods: The risk of MM from organochlorine compounds was examined in a population-based case–control study in British Columbia, Canada. Congeners of PCBs and pesticides or pesticide metabolites were measured in plasma of 325 cases and 327 controls. Results: Most organochlorine analytes showed a significant association with MM. The strongest association (highest vs lowest quartile) was oxychlordane (odds ratio = 7.44; 95% confidence interval = 4.19 to 13.21). No heterogeneity was detected between organochlorines levels and MM subtypes. Only oxychlordane and β-hexachlorocyclohexane (β-HCCH) were identified as significant independent predictors of MM. Conclusion: Our study provides evidence that organochlorines contribute to the risk of MM. Abstract : Supplemental Digital Content is available in the text